ANALYSIS OF THE PRACTICE OF EDUCATIONAL PROCESS OF CONSTRUCTION OF A SHOW ANNUAL SCHOOL OF CAMPO GRANDE – MS (Fiep Bulletin - online, 2015)
This study sought to analyze how the pedagogical practices of teachers from a school in Campo Grande - MS confirmed for construction of the spectacle of it occurring annually process. Such a school uses a theoretical basis of education for their actions and institutional organizations, and this Constructivism. Taking place in the midst of a discipline, this work was generated to compose one of the evaluations contained in the discipline called "Deepening in Dance" in which students attended, given by the guiding teacher of this study. This work is characterized as a case study, and as a research tool A semi-structured interview. The aim of this study was to analyze the correlation of educational practice utilized by the teachers in the building's annual show with the theoretical current process adopted by the school. From the analysis of data from the three teachers we can observe that the pedagogical practice in the same building of the show matched partially with the theoretical current advocated by the school.
Keywords: Pedagogical Practice. School.Dance performance.